Charles Binns papers - Binns, Charles
Ledger belonging to Charles Binns, containing accounts for money lending, fees for legal services in Loudoun and Fairfax counties, Va., and trade in agricultural products (1785-1786); individual ledger sheets for noted agriculturalist John Alexander Binns; accounts for free African Americans; and Binns family genealogical material (1840s).
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Farmer, landowner, and clerk of Loudoun County, Va.
Collection material in English.
Keywords: Binns, John Alexander, -- approximately 1761-1813.; Binns family; Costs (Law) -- Virginia -- Fairfax County; Costs (Law) -- Virginia -- Loudoun County; Farm produce -- Virginia; Free African Americans -- Virginia; County clerks; Farmers